Worker-Level Consequences of Import Shocks - Katariina Nilsson Hakkala; Kristiina Huttunen (Institute for the Study of Labor (IZA), 2016)
We analyse the effects of imports on employment and earnings by distinguishing between import competition in final products and firms' use of imports in production (offshoring). We use Finnish worker-firm data merged with product-level trade data. We focus on Chinese imports and instrument them by changes in China's share of world exports to other EU countries. Both types of importing increase the job loss risk for all workers and, in particular, for workers in production occupations. An increase in import competition has larger negative effects than an increase in offshoring. Production workers suffer the largest earnings losses, while for high- skilled workers the wage-effect is positive.
Keywords: F16; J23; J31; J63; L23; 330; offshoring; import competition; employment; earnings